Overexpression of patatin‐related phospholipase AIIIδ altered plant growth and increased seed oil content in camelina. Issue 6 (29th December 2014) - Li, Maoyin; Wei, Fang; Tawfall, Amanda; Tang, Michelle; Saettele, Allison; Wang, Xuemin
Summary Camelina sativa is a Brassicaceae oilseed species being explored as a biofuel and industrial oil crop. A growing number of studies have indicated that the turnover of phosphatidylcholine plays an important role in the synthesis and modification of triacylglycerols. This study manipulated the expression of a patatin‐related phospholipase AIIIδ (pPLAIIIδ) in camelina to determine its effect on seed oil content and plant growth. Constitutive overexpression of pPLAIIIδ under the control of the constitutive cauliflower mosaic 35S promoter resulted in a significant increase in seed oil content and a decrease in cellulose content. In addition, the content of major membrane phospholipids, phosphatidylcholine and phosphatidylethanolamine, in 35S::pPLAIIIδ plants was increased. However, these changes in 35S::pPLAIIIδ camelina were associated with shorter cell length, leaves, stems, and seed pods and a decrease in overall seed production. When pPLAIIIδ was expressed under the control of the seed specific, β‐conglycinin promoter, the seed oil content was increased without compromising plant growth. The results suggest that pPLAIIIδ alters the carbon partitioning by decreasing cellulose content and increasing oil content in camelina.